Initial analgesic prescriptions for osteoarthritis in the United Kingdom, 2000–2016. (28th June 2020) - Zeng, Chao; Zhang, Weiya; Doherty, Michael; Persson, Monica S M; Mallen, Christian; Swain, Subhashisa; Li, Xiaoxiao; Wei, Jie; Lei, Guanghua; Zhang, Yuqing
Abstract: Objectives: To examine trends in the initial prescription of commonly-prescribed analgesics and patient- as well as practice-level factors related to their selection in incident OA. Methods: Patients consulting with incident clinical OA between 2000–2016 were identified within The Health Improvement Network in the United Kingdom (UK) general practice. Excluded were patients who had history of cancer or were prescribed the analgesics of interest within 6 months before diagnosis of OA. Initial analgesic prescription included oral non-selective NSAID, oral selective cyclooxygenase-2 inhibitor, topical NSAID, paracetamol, topical salicylate or oral/transdermal opioid within 1 month after OA diagnosis. Results: ∼44% of patients with incident OA ( n = 125 696) were prescribed one of these analgesics. Incidence of oral NSAID prescriptions decreased whereas other analgesic prescriptions, including oral opioid prescriptions, increased (all P -for-trend < 0.001). Patients with a history of gastrointestinal disease were more likely to receive topical NSAIDs, paracetamol or oral/transdermal opioids. Only 38% of patients with history of gastrointestinal disease and 21% of patients without it had co-prescription of gastroprotective agent with oral NSAIDs. Oral/transdermal opioid prescription was higher among the elderly (≥65 years), women, obesity, current smoker, and patients with gastrointestinal, cardiovascular or chronic kidney disease. Prescription of oral opioids increased with social deprivation ( P -for-trend < 0.05) and was highest in Scotland, whereas transdermal opioid prescription was highest in Northern Ireland (all P -for-homogeneity-test < 0.05). Conclusion: The initial prescription pattern of analgesics for OA has changed over time in the UK. Co-prescription of gastroprotective agents with oral NSAIDs remains suboptimal, even among those with prior gastrointestinal disease.